Anxiety of Chittagong University Students - Dey, Biplob Kumar (Chittagong University Journal of Biological Sciences, 2024)
The present study attempted an empirical investigation to identify the factors influencing anxiety level among students of Chittagong University. A total of 120 respondents constituted the sample of the study. Among the 120 students, 60 students were male (30 were from residential and 30 were from non-residential) and 60 students were female (30 were from residential and 30 were from non-residential). In each group, 10 students were from Science Faculty, 10 students were' from Commerce Faculty and 10 students were from Arts Faculty. The Bangla Anxiety Scale developed by (Deeba and Begum 2004) was used to measure anxiety of the respondents. The data were analyzed using mean, standard deviation, t-value and one-way analysis of variance (ANOVA). The findings of the present study showed that more female students was significantly higher anxiety level (t = 3.38, df = 118, p < 0.05) than male students. On the other hand, residential students expressed higher anxiety (t = 4.22, df =118, p<0.05) as compared to non-residential students of Chittagong University. The students of Arts faculty expressed more anxiety as compared to Science and Commerce Faculties (F=4.83, df=2, ·p·<-0.05). The Chittagong Univ. J B. Sci. 8(1&2): 117-126, 2013